The Effect of Aerobic and Walking Exercise on Physical and Psychological Symptoms and Pain of Premenstrual Syndrome - Yekke Fallah L; Azimi H; Sadeghi T (Iran University of Medical Sciences, 2013)
Background & Aims: Premenstrual Syndrome may have disabling effects on the person's performance in the family and community . To relief from the symptoms of this syndrome, different methods such as safe exercise have been recommended. The aim of this study was to determine the effect of a three -month regular aerobic and walking exercise on physical and psychological symptoms and pain of premenstrual syndrome .   Material and Methods: this Quasi-Experimental study was conducted on 7 0 volunteer 18-32 years old female students with at least 40% PMS symptoms. The Participants were randomly assigned into 3 groups of aerobic, walking and control. Aerobic group exercise 7 types of practice for 30 minutes daily for 3 months. The walking group practiced fast walking 30 minutes daily for 3 months. All of Participants completed the standard questionnaire of "Jack. Tips" for 3 times (before, 1 and 3 months after intervention).Data were analyzed using SPSS win (v.16) using one-way ANOVA. Significance level was considered as less than 0.05.   Results: Pain reduction was significant at the end of first and third month of intervention (p=0.008, p=0.047). A significant difference was observed for physical symptoms after one menstruation cycle (p=0.001) although it was not significant after three menstruation cycles. No significant differences were observed in psychological symptoms after 1 and 3 cycles. Repeated measurement showed significant difference in physical symptoms of the 3 (P = 0.034).  Conclusion: Three months of walking and aerobic exercise are very effective in reducing pain and Physical symptoms of premenstrual syndrome. Although aerobic exercise is more effective in reducing pain , but it does not create a significant improvement in psychological symptoms. Performing these two exercises are recommended to reduce the symptoms of premenstrual syndrome.  Received: 5 Mar 2013   Accepted: 1 Jun 2013